STRATEGI PENGEMBANGAN USAHATANI JAGUNG DI DESA MALIK TRANS KECAMATAN BUALEMO KABUPATEN BANGGAI - I Wayan suartana; Made Antara; lien Damayanti (Universitas Tadulako, 2016)
The research aimed was to identify the strategy of corn agribusiness development in Bualemo sub district of Banggai Regency. It was a descriptive-qualitative research. Respondent samples were determined using a simply random sampling technique. Based on SWOT analysis, the strategy for the corn farming system development was S-T (Strength – Threats) strategy. The strategy recommended for the development of the corn farming system in Bualemo were (1) increasing corn production by means of applying plant cultivation technology; and (2) determining zonation of location for priority corn development. Programs needed to be addressed were (1) integrated corn pest control; (2) improving field officer competency; and (3) land suitability evaluation. Keywords: Corn Farming, Development Strategy, and SWOT Analysis.